A Reconfigurable Triple Band Notched Elliptical Planar Monopole Antenna for UWB Applications - D. Sreenivasa Rao, Dr. I. Govardhani, Dr. M. Venkata Narayana, B. P S Sandeep, CH. Rohit Reddy and Y. N Dheeraj (International Journal of Advanced Science and Technology, 2020)
This paper consists of a new design of an elliptical reconfigurable triple-band notch antenna for Ultra-Wide-Band (UWB) applications. This antenna designed on 38 X 40 mm2 Fire-Resistant (FR4) epoxy substrate. It can avoid the inferences which rise from the Wi-MAX (3.3GHz-3.7GHz), WLAN (5GHz-6GHz) and X-band satellite communication uplink band (7.9GHz-8.4GHz). One vertical slot placed on the ground and two U-shaped slots, one is placed on a patch and another on a feed line to obtain band-stop function at Wi-MAX, WLAN and X-Band satellite communication bands. Three slots are integrated with three PIN diodes to achieve reconfigurable band-notched characteristics. This antenna is designed and optimized using electromagnetic simulation software Ansoft HFSS. The designed antenna has impedance bandwidth from 2.6-12GHz. We observed good radiation characteristics.